Large retroperitoneal dermoid cyst in a 55 year old lady: a rare case report - Mehta, Harsh Rajeev; Iyer, Sriranjani; Jadhav, Sarojini P.; Ansari, Mohammed M. (International Surgery Journal, 2020)
Retroperitoneal cysts are usually rare asymptomatic lesions but may present with unspecific symptoms depending on the size, location and complications such as hemorrhage, infection, or rupture. A 55-year-old lady presented with complaints of non-obstructed umbilical hernia. CT scan of abdomen and pelvis was done suggestive of a large cystic non-enhancing thin walled lesion of size 27×15 cm in right lumbar region. Intraoperatively, there was a large mesenteric cyst from retroperitoneum of size 25×15 cm, extending from right iliac fossa up to right hypochondrium. A confirmatory diagnosis of dermoid cyst was made following histopathology. Retroperitoneum is a rare site for dermoid cyst. Retroperitoneal cysts which develop within the retroperitoneal space are rare intra-abdominal tumours with an incidence of 1 per 1,40,000. The incidence of recurrence for retroperitoneal cysts is higher than with other forms of cysts because their proximity to major blood vessels and other organs makes them difficult to completely excise. Surgical resection is indicated to establish a diagnosis and prevent eventual complications. Complete excision of tumour is necessary due to the risk of malignancy. After complete surgical resection the 5 years survival rate is nearly 100%.